Dynamic Analysis of the Crank Mechanism through the Numerical Solution - Minárik, Marián; Bodnár, Ferdinand (Manufacturing Technology Journal, 2019)
Dynamic analysis of crank mechanism is realised by relaxation method, where a connecting rod is modelled with three manners. In the first case the connecting rod is modelled as a rigid body, in the second case this one is modelled with two mass points and in the third case the connecting rod is modelled with three mass points. Results of all manners of modelling are compared and evaluated.
Keywords: Crank Mechanism; Dynamic Analysis; Kinematic Quantities